2011
DOI: 10.1111/j.1600-6143.2011.03590.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-Induced Hypophosphatemia and Insulin Resistance Are Associated With mTORC2 Activation and Klotho Expression

Abstract: Rapamycin, an immunosuppressive drug used to prevent rejection after kidney transplantation, influences phosphate homeostasis, induces insulin resistance and has been shown to prolong lifespan in animal models. Because Klotho is an aging-suppressor gene controlling phosphate metabolism and insulin sensitivity, we investigated the influence of rapamycin on Klotho expression. A total of 100 kidney transplant recipients, 50 chronically treated with rapamycin and 50 with calcineurin inhibitors, were enrolled; 20 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…14,36,37 Thus, rapamycin-induced phosphaturia may also indirectly attenuate VC in vivo. However, in the present study, the serum Pi level from adenine-induced rat CRF model does not show significant difference between vehicle and rapamycin treatment groups (Table 1).…”
Section: Rapamycin Reverses Pi-induced Calcification Through Klotho Umentioning
confidence: 96%
See 2 more Smart Citations
“…14,36,37 Thus, rapamycin-induced phosphaturia may also indirectly attenuate VC in vivo. However, in the present study, the serum Pi level from adenine-induced rat CRF model does not show significant difference between vehicle and rapamycin treatment groups (Table 1).…”
Section: Rapamycin Reverses Pi-induced Calcification Through Klotho Umentioning
confidence: 96%
“…12,13 Recently, using animal models, inhibition of mTOR by rapamycin markedly ameliorates the interstitial inflammation, fibrosis, and loss of renal function associated with CKD. 20 In addition, rapamycin might be involved in regulating phosphate homeostasis 14 and might be associated with renal function reserve in rat, 19 suggesting that mTOR signaling is involved in renal dysfunction in CKD. Thus, it is valuable to explore the role of rapamycin and mTOR signaling in VC of CKD individuals.…”
Section: Rapamycin Reverses Pi-induced Calcification Through Klotho Umentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that klotho was associated with various kidney diseases including glomerulonephritis, ischemic kidney disease, hypertensive and diabetic nephropathy, and even polycystic kidney disease [5-7, 24, 31]. The underlying mechanisms are not clear, however, it has been shown that klotho involved with wide-ranging phenomena such as oxidative stress, apoptosis, inflammation, and fibrosis implicated in renal pathology [25,[32][33][34], and the interaction of klotho with renin-angiotensin system or mTOR signaling was suggested to modulate those processes [35][36]. Genetic variations of klotho could influence on the progression of chronic kidney disease through these mechanisms, and it was reflected in a report that SNPs of klotho affected the severity of non-diabetic ESRD [37] as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…40 Inhibitors of the mTOR pathway, including everolimus, also cause hypophosphataemia in nonrenal transplant recipients, 41,42 probably through an effect of mTOR inhib ition on the expression of Klotho, the cofactor of the FGF-23 receptor, in tubular epithelial cells ( Figure 2). 43 The majority of immunosuppressive drugs have, therefore, been linked to hypophosphataemia after kidney transplantation. Interestingly, such effects have not been reported in patients who received a similar immuno suppressive regimen following non-renal transplantation, suggesting a key role of the recovering kidney in this process.…”
Section: Kidney Transplantationmentioning
confidence: 99%